MAKNA RUHANI DALAM RITUAL DAN ESKATOLOGI ISLAM MENURUT AL-ALUSI - Ibnu Arabi (UIN Antasari Banjarmasin, 2023)
Abstract: Religious life is related to issues of ritual and eschatology. These two things are comprehended and addressed differently in various circles. Among Fiqh scholars, worship (ibadah) is known as a form of formality without the ability to be creative. While some philosophers argue that worship is an irrational act. In the view of Sufism, worship in religion is something meaningful, it's just that not everyone can explore this meaning, because indeed in religion the issue of worship is understood as something supra-rational. This research uses the tafsir isyari approach and the chosen tafsir is tafsir Ruh al-Ma'ani written by al-Alusi. Data collection in the study was done by tracing the verses of the Qur'an interpreted by al-Alusi in his tafsir with isyari interpretation. From the research, it is concluded that the interpretation of Ruh al-Ma'ani by al-Alusi is one of the great books of tafsir that contains the zhahir and isyarah interpretations. The isyarah interpretation is within reasonable parameters, not in the form of a Bathiniyah interpretation.Keywords: Ruhani Meanings, Rituals, Islamic Eschatology. Abstrak: kehidupan beragama terkait dengan persoalan ritual dan eskatologi. Dua hal tersebut dalam berbagai kalangan dipahami dan disikapi secara berbeda. Di kalangan fiqh, ibadah dikenal sebagai bentuk formalitas tanpa kebolehan berkreasi. Sementara kalangan filosof ada yang berpendapat bahwa ibadah adalah tindakan irrasional. Dalam pandangan sufisme, ibadah dalam agama adalah sesuatu yang bermakna, hanya saja tidak semua orang mampu menyelami maknanya tersebut, karena memang dalam beragama persoalan ibadah dipahami sebagai sesuatu yang supra rasional. Penelitian ini menggunakan pendekatan tafsir isyari dan tafsir yang dipilih adalah tafsir Ruh al-Ma'ani yang ditulis oleh al-Alusi. Pengumpulan data dalam penelitian melalui;1) menelurusi ayat-ayat Alquran yang ditafsirkan oleh al-Alusi dalam tafsirnya dengan penafsiran isyari. Dari penelitian tersebut disimpulkan bahwa tafsir Ruh al-Ma’ani karya al-Alusi, adalah salah satu kitab tafsir besar yang memuat penafsiran-penafsiran zhahir dan isyarah. Penafsiran isyarahnya batas-batas kewajaran, tidak dalam dalam wujud tafsir Bathiniyah.Keywords: Makna Ruhani, Ritual, Eskatologi Islam.